Human Platelets Exposed to Mechanical Stresses Express a Potent Lipoxygenase Product - Margalit, Alon; Livne, Avinoam A (Thrombosis and Haemostasis, 1992)
Human platelets exposed to hypotonicity undergo regulatory volume decrease (RVD), controlled by a potent, yet labile, lipoxygenase product (LP). LP is synthesized and excreted during RVD affecting selectively K+ permeability. LP is assayed by its capacity to reconstitute RVD when lipoxygenase is blocked. Centrifugation for preparing washed platelets (1,550 × g, 10 min) is sufficient to express LP activity, with declining potency in repeated centrifugations, indicating that it is not readily replenish-able. When platelet suspension flows in a vinyl tubing (1 mm i.d.), at physiological velocity, controlled at 90–254 cm/s, LP formation increases as a function of velocity but declines as result of increasing the tubing length. Stirring the platelets in an aggregometer cuvette for 30 s, yields no LP unless the stirring is intermittent. No associated platelet lysis or aggregation are observed following the mechanical stress applications. These results demonstrate that although mechanical stresses result in LP production, the mode of its application plays a major role. These results may indicate that LP is synthesized under pathological conditions and could be of relevance to platelets behavior related to arterial stenosis.